2020
DOI: 10.1016/j.pediatrneurol.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Neurology Research in the Twenty-First Century: Status, Challenges, and Future Directions Post–COVID-19

Abstract: Background:The year 2020 marked a fundamental shift in the pediatric neurology field. An impressive positive trajectory of advances in patient care and research faced sudden global disruptions by the coronavirus disease 2019 pandemic and by an international movement protesting racial, socioeconomic, and health disparities. The disruptions revealed obstacles and fragility within the pediatric neurology research mission. However, renewed commitment offers unique opportunities for the pediatric neurology research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Clinicians can observe their patients with preexisting seizure disorders through regular telemedicine (Parihar et al, 2020). Moreover, because COVID-19 could cause neurological complications in children as well, pediatric neurology should pay more attention to their patients' manifestations for a timely diagnosis and treatment (Bonkowsky et al, 2020).…”
Section: Treatment and Clinical Managementmentioning
confidence: 99%
“…Clinicians can observe their patients with preexisting seizure disorders through regular telemedicine (Parihar et al, 2020). Moreover, because COVID-19 could cause neurological complications in children as well, pediatric neurology should pay more attention to their patients' manifestations for a timely diagnosis and treatment (Bonkowsky et al, 2020).…”
Section: Treatment and Clinical Managementmentioning
confidence: 99%
“…Since the formal development of organized child neurology (CN) training programs in the late 1950s, 1 monumental changes have occurred in science, diagnostics, and therapeutics in pediatric neurology. 2 While the field of CN originally emerged as a subspecialty of adult neurology, 3 pediatric neurology divisions have grown in both size of faculty and number of residents in training, and many are established within departments of pediatrics in large urban children's hospitals. 4 Reflecting these changes, the 2015 American Academy of Pediatrics and Child Neurology Society (CNS) Workforce Survey demonstrated that CN residents and practicing physicians favor an increased training emphasis on child-centric disciplines such as genetics and developmental disorders and a decrease in the amount of adult neurology training.…”
Section: Discussionmentioning
confidence: 99%
“…Since the formal development of organized child neurology (CN) training programs in the late 1950s, 1 monumental changes have occurred in science, diagnostics, and therapeutics in pediatric neurology. 2 While the field of CN originally emerged as a subspecialty of adult neurology, 3 pediatric neurology divisions have grown in both size of faculty and number of residents in training, and many are established within departments of pediatrics in large urban children's hospitals. 4…”
mentioning
confidence: 99%
“…neurology research and the funding post COVID-19 in the developed countries. 1 We would like to address the setbacks in the training of pediatric neurology residents and fellows and research activities in the teaching hospitals from developing countries.…”
mentioning
confidence: 99%